RD26 mediates crosstalk between drought and brassinosteroid signalling pathways - Ye, H. X.; Liu, Sanzhen Z.; Tang, B. Y.; Chen, J. N.; Xie, Z. L.; Nolan, T. M.; Jiang, H.; Guo, H. Q.; Lin, H. Y.; Li, L.; Wang, Y. Q.; Tong, H. N.; et al. (My University, 2017)
Brassinosteroids (BRs) regulate plant growth and stress responses via the BES1/BZR1 family of transcription factors, which regulate the expression of thousands of downstream genes. BRs are involved in the response to drought, however the mechanistic understanding of interactions between BR signalling and drought response remains to be established. Here we show that transcription factor RD26 mediates crosstalk between drought and BR signalling. When overexpressed, BES1 target gene RD26 can inhibit BR-regulated growth. Global gene expression studies suggest that RD26 can act antagonistically to BR to regulate the expression of a subset of BES1-regulated genes, thereby inhibiting BR function. We show that RD26 can interact with BES1 protein and antagonize BES1 transcriptional activity on BR-regulated genes and that BR signalling can also repress expression of RD26 and its homologues and inhibit drought responses. Our results thus reveal a mechanism coordinating plant growth and drought tolerance.
Citation: Ye, H. X., Liu, S. Z., Tang, B. Y., Chen, J. N., Xie, Z. L., Nolan, T. M., . . . Yin, Y. H. (2017). RD26 mediates crosstalk between drought and brassinosteroid signalling pathways. Nature Communications, 8, 1-13. http://doi.org/10.1038/ncomms14573
Keywords: Regulated Gene-Expression; Nac Transcription Factors; Abiotic Stress; Responses; Receptor Kinase Bri1; Arabidopsis-Thaliana